Anti-Inflammatory Activities of a Chinese Herbal Formula IBS-20 In Vitro and In Vivo. (22nd February 2012) - Yang, Zhonghan; Grinchuk, Viktoriya; Ip, Siu Po; Che, Chun-Tao; Fong, Harry H. S.; Lao, Lixing; Wu, Justin C.; Sung, Joseph J.; Berman, Brian; Shea-Donohue, Terez; Zhao, Aiping
Abstract : Irritable bowel syndrome (IBS) is a functional bowel disorder and the etiology is not well understood. Currently there is no cure for IBS and no existing medication induces symptom relief in all patients. IBS-20 is a 20-herb Chinese medicinal formula that offers beneficial effects in patients with IBS; however, the underlying mechanisms are largely unknown. This study showed that IBS-20 potently inhibited LPS- or IFNΓ-stimulated expression of pro-inflammatory cytokines, as well as classically activated macrophage marker nitric oxide synthase 2. Similarly, IBS-20 or the component herb Coptis chinensis decreased LPS-stimulated pro-inflammatory cytokine secretion from JAWS II dendritic cells. IBS-20 or the component herbs also blocked or attenuated the IFNΓ-induced drop in transepithelial electric resistance, an index of permeability, in fully differentiated Caco-2 monolayer. Finally, the up-regulation of key inflammatory cytokines in inflamed colon from TNBS-treated mice was suppressed significantly by orally administrated IBS-20, including IFNΓ and IL-12p40. These data indicate that the anti-inflammatory activities of IBS-20 may contribute to the beneficial effects of the herbal extract in patients with IBS, providing a potential mechanism of action for IBS-20. In addition, IBS-20 may be a potential therapeutic agent against other Th1-dominant gut pathologies such as inflammatory bowel disease.